Ethniciser le territoire - Jean-Pierre Goulard (Cahiers des Amériques Latines, 2005)
The area named the «region of the Amazonian trapezium» is to be set apart from its global environment because of specific characteristics and, as a consequence, presents to the social scientist a place of work of unusual interest. The author sketches the inhabitants’ life and the patterns of their spatial distribution, and then analyzes several aspects of each concerned group, over the geopolitical borders. The partition of the territory helps in bringing to life and developing processes of interactions based on «reciprocal perceptions». This mutual understanding makes able to discern bases for some identity’s horizon which might lead to the emergence of a regional identity.